2018
DOI: 10.26434/chemrxiv.7106318.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Elucidating CO2 Chemisorption in Diamine-Appended Metal–Organic Frameworks

Abstract: The widespread deployment of carbon capture and sequestration as a climate change mitigation strategy could be facilitated by the development of more energy-efficient adsorbents. Diamine-appended metal-organic frameworks of the type diamine-M2(dobpdc) (M = Mg, Mn, Fe, Co, Ni, Zn; dobpdc 4− = 4,4′-dioxidobiphenyl-3,3′-dicarboxylate) have shown promise for carbon capture applications, although questions remain regarding the molecular mechanisms of CO2 uptake in these materials. Here, we leverage the crystallinit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(31 citation statements)
references
References 49 publications
(126 reference statements)
3
28
0
Order By: Relevance
“…In 2017 and 2018, they reported a series of diamineappended variants of MOF Mg 2 (dobpdc) (dobpdc 4− = 4,4′-dioxidobiphenyl-3,3′-dicarboxylate) and found the different appended diamine could cause new adsorption mechanisms. [93,94] Later, in 2020, Long and co-workers reported a series of alcoholamine-and alkoxyalkylamine-functionalized MOF Mg 2 (dobpdc). [95] The modified materials were confirmed isoreticular to previous analogs by powder X-ray diffraction (PXRD).…”
Section: Regulation Of Appended Functionalizationmentioning
confidence: 99%
“…In 2017 and 2018, they reported a series of diamineappended variants of MOF Mg 2 (dobpdc) (dobpdc 4− = 4,4′-dioxidobiphenyl-3,3′-dicarboxylate) and found the different appended diamine could cause new adsorption mechanisms. [93,94] Later, in 2020, Long and co-workers reported a series of alcoholamine-and alkoxyalkylamine-functionalized MOF Mg 2 (dobpdc). [95] The modified materials were confirmed isoreticular to previous analogs by powder X-ray diffraction (PXRD).…”
Section: Regulation Of Appended Functionalizationmentioning
confidence: 99%
“…Figure 2a shows a common ex situ approach for studying solid-adsorbents for CO2 capture, which we term "ex situ MAS". 13,17,21 In this approach, a MAS rotor is packed with the solid adsorbent and is transferred to a gas-dosing manifold, with the rotor left open. The sample is then evacuated before dosing CO2 gas.…”
Section: Practical Considerations For Nmr Studies Of Carbon Dioxide C...mentioning
confidence: 99%
“…As discussed previously, 13 C NMR experiments can be implemented easily and provide a wealth of information about the number and type of carbon environments present in sorbent materials. More detailed information about the binding mechanisms can be gained by exploring the local connectivity of the carbon atoms through correlation experiments.…”
Section: And 1 H Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…28−30 For example, Fragai et al 31 showed that the three-dimensional structures of the enzymes were retained after immobilization in a peptide-templated silica gel. Indeed, ssNMR spectroscopy has been applied as a general approach to study MOFs and their interactions with small guest species 32 (e.g., H 2 , 33 xenon, 34 CO, 35 CO 2 , 36,37 nitric oxide, 38 H 2 O, 39 hydrocarbon, 40 aromatics, 41,42 etc. ), providing complementary information for host−guest interaction.…”
Section: ■ Introductionmentioning
confidence: 99%